Emily Dickinson po polsku - Salska, Agnieszka (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The article traces Polish translations of Dickinson’s poetry preceding and following the publication in the nineteen nineties of 200 poems by Emily Dickinson translated by Stanisław Barańczak. It comments on some Polish poets’ response to Dickinson in their own works and points to the growing body of publications online of private selections from Dickinson’s poems previously translated by established Polish poets (mostly Barańczak or Marjańska) as well as translations and original poems inspired by Dickinson’s work authored by less known poets, amateur translators and lovers of poetry. The article suggests that the increased Polish interest in Dickinson’s work is not only a kind of domino effect following Barańczak’s impressive translations. It also results from the growth of interest in translation studies and skills and must be related, too, to the fact that her poetry of private sensibility confronted with a dramatically changing world resonates with contemporary experience of the sensitive individual.